2017
DOI: 10.1007/s10826-017-0910-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Paternal Predictors of Child Depressive Symptoms: An Actor-Partner Interdependence Framework

Abstract: Family members are theorized to influence each other via transactional or systems related processes; however, the literature is limited given its focus on mother-child relationships and the utilization of statistical approaches that do not model interdependence within family members. The current study evaluated associations between self-reported parental affect, parenting behavior, and child depressive symptoms among 103 mother-father-child triads. Children ranged in age from 8 to 12 years. Higher maternal neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…A large body of reviews and empirical studies investigating the association of parenting and adolescent depression showed that warmth, care, acceptance and other positive parenting behaviors were negatively linked to depression (Milevsky et al, 2007; Brand et al, 2009a,b; Yap et al, 2014; Wang Y.C. et al, 2015; Little et al, 2017), while negative parenting characterized by harsh, control and neglect were risks for depression (Aunola et al, 2013; Reising et al, 2013; Frazer and Fite, 2016; Murdock et al, 2018). Regardless of the differences in dimension of parenting practice, there is consistency that parental care and control have a close association with individual depression.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of reviews and empirical studies investigating the association of parenting and adolescent depression showed that warmth, care, acceptance and other positive parenting behaviors were negatively linked to depression (Milevsky et al, 2007; Brand et al, 2009a,b; Yap et al, 2014; Wang Y.C. et al, 2015; Little et al, 2017), while negative parenting characterized by harsh, control and neglect were risks for depression (Aunola et al, 2013; Reising et al, 2013; Frazer and Fite, 2016; Murdock et al, 2018). Regardless of the differences in dimension of parenting practice, there is consistency that parental care and control have a close association with individual depression.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it might be that only a punitive style (including physical punishment and yelling in the APQ‐Pr) has a long‐term impact on child emotion regulation skills. Studies showing a mediating effect of parenting in the relationship between maternal and child internalizing symptoms are either cross‐sectional or have shorter follow‐up periods (Murdock et al, 2018; Zalewski et al, 2017). Internalizing difficulties were assessed in preadolescence, when the social world starts having a more prominent role in the emotional well‐being, beyond family relationships (Ross, Shochet, & Bellair, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Ramchandani and Psychogiou (2009) reviewed a number of studies suggesting higher risk of emotional and behavioural difficulties for boys in the context of paternal psychopathology. Murdock, Pittman, and Fagundes (2018) demonstrated a direct relationship between maternal negative affect and child depressive symptoms, but only an indirect association between paternal and child depressive symptoms, which was mediated by punitive parenting. It would appear that maternal symptoms impact directly on both girls and boys (Andreas et al, 2018; Watson, Potts, Hardcastle, Forehand, & Compas, 2012), whereas fathers’ symptoms have an indirect effect (Murdock et al, 2018) and a stronger influence on boys’ difficulties (Ramchandani & Psychogiou, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Neither family income nor paternal education is consistently associated with children's psychopathology. While some evidence shows beneficial effects of higher income and paternal education (Bradley & Corwyn, 2002;Reising et al, 2013;Slopen et al 2010), other studies did not find this effect (Murdock et al, 2018;Weitzman et al, 2011). Furthermore, parental age does not appear to be associated with children's emotional and behavior problems (Boivin et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…The age of onset of psychopathology is usually in adolescence or early adulthood (Jacobi et al, 2004), with prevalence rates of depression in 13–18-year-olds being twice as high as in children under 13 years (5.6% vs. 2.8%, Jane Costello et al, 2006). Accordingly, in a US nationally representative sample, Weitzman et al (2011) found that higher age (12–17 vs. 5–11 years) was mildly associated with emotional and behavioral problems, whereas another study found that children’s age was not associated with depressive symptoms in children aged 8–12 years (Murdock et al, 2018). Finally, there is an important overlap between physical health and mental health outcomes in children and adolescents (Merikangas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%